1999
DOI: 10.1002/(sici)1097-0061(199908)15:11<1133::aid-yea438>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of homologs of RAS and RHO1 genes from Cryptococcus neoformans

Abstract: We cloned and sequenced homologs of RAS(CnRAS) and RHO1(CnRHO1) genes from Cryptococcus neoformans. The proteins encoded by the CnRAS and CnRHO1 genes contained 216 and 197 amino acids, respectively. The deduced amino acid sequence of the CnRAS gene shared a high degree of sequence identity with the Ras proteins in other fungal species: Coprinus cinereus(76%), Lentinula edodes(74%), Saccharomyces cerevisiae RAS2(72%), and Schizosaccharomyces pombe(68%). The deduced amino acid sequence of the CnRHO1 gene shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, the induction of capsule around the cell does not appear to be due solely to the induction of the various biosynthetic genes. The next sections discuss the signaling pathways that regulate capsule and the transcriptional outputs that result in capsule induction (see Table S2 in the supplemental material) (44,119,194). …”
Section: Regulation Of Capsule Induction In Specific Environmentsmentioning
confidence: 99%
“…However, the induction of capsule around the cell does not appear to be due solely to the induction of the various biosynthetic genes. The next sections discuss the signaling pathways that regulate capsule and the transcriptional outputs that result in capsule induction (see Table S2 in the supplemental material) (44,119,194). …”
Section: Regulation Of Capsule Induction In Specific Environmentsmentioning
confidence: 99%
“…The NC-ras2 gene of Neurospora crassa regulates hyphal growth, cell wall synthesis, and the formation of conidia (25). In Cryptococcus neoformans, RAS1 is required for growth at elevated temperatures, mating, filamentation, agar invasion, and sporulation (1,49). The Schizosaccharomyces pombe ras1 gene is involved in pheromone response, morphogenesis, and sporulation (16,57).…”
Section: Vol 1 2002mentioning
confidence: 99%
“…This result suggested that a cloned cDNA of C. neoformans could functionally suppress the temperature-sensitive mutation rho1-104 in S. cerevisiae. The sequence of the cloned C. neoformans cDNA insert showed great similarity to the RHO1 gene of S. cerevisiae and was almost identical to the published sequence of CnRHO1 cDNA of C. neoformans, which was obtained by PCR amplification (35). The differences between the cloned cDNA and the published CnRHO1 cDNA sequence were at positions 266 (T3C) and 500 (G3C) (35).…”
mentioning
confidence: 55%
“…The regulatory subunit is encoded by RHO1 (10,27,32). Recently, sequence analysis of the Cryptococcus neoformans RHO1 cDNA (CnRHO1) indicated that the putative protein encoded by CnRHO1 contains 197 amino acids and shares a high degree of sequence identity with Rho1p in other fungal species (35). The function of CnRHO1 in C. neoformans, however, was not elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation